2021
DOI: 10.1016/j.ejca.2021.01.037
|View full text |Cite
|
Sign up to set email alerts
|

Immune analysis of lymph nodes in relation to the presence or absence of tumor infiltrating lymphocytes in triple-negative breast cancer

Abstract: Triple-negative breast cancer (TNBC) is a subtype of breast cancer with unmet medical needs. Several studies have proved that high levels of tumor infiltrating lymphocytes (TILs) at diagnosis of TNBC confer better prognosis and patients respond better to specific chemotherapies. Nonetheless, current evidence suggests that only 15% of TNBC patients have

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Within an individual tumor, heterogeneity occurs at the level of the genome, transcriptome and proteome, which leads to the diversity of cell populations and tissue morphology [3,9,14,15]. As an example, recent studies have shown that tumor-infiltrating lymphocytes (TILs) in the primary tumor play an important role in therapy response and prognosis in breast cancer [4,[16][17][18][19][20][21][22][23][24][25][26]]. Yet, improved clinical outcomes were associated with the presence of TILs in some but not all tumor types and in some but not all patients [4,[27][28][29][30].…”
Section: Introduction 1biology and Prognostic Biomarkers In Breast Cancermentioning
confidence: 99%
“…Within an individual tumor, heterogeneity occurs at the level of the genome, transcriptome and proteome, which leads to the diversity of cell populations and tissue morphology [3,9,14,15]. As an example, recent studies have shown that tumor-infiltrating lymphocytes (TILs) in the primary tumor play an important role in therapy response and prognosis in breast cancer [4,[16][17][18][19][20][21][22][23][24][25][26]]. Yet, improved clinical outcomes were associated with the presence of TILs in some but not all tumor types and in some but not all patients [4,[27][28][29][30].…”
Section: Introduction 1biology and Prognostic Biomarkers In Breast Cancermentioning
confidence: 99%
“…TNBC patients with stromal TIL levels higher than 20% have more germinal centres in their cancer-free LNs, while the identification of TLSs in the TME correlates with an increased number of germinal centres in metastatic LNs [ 50 ]. In alignment with this, Quintana et al studied similar features in a LN-negative TNBC cohort and found that TNBC patients with >50% TILs have more and larger germinal centres in their LNs and more TLSs at their primary tumour site compared to patients with <5% TILs [ 57 ]. We, too, have evidenced immune activation via the formation of germinal centres in LNs in level 1 of the axilla (closest to the primary tumour), as compared to level 3 LNs (most distal to the primary carcinoma) which do not show any germinal centre formation [ 54 ].…”
Section: Lymph Nodes: the Immune Capital Of Anti-tumour Responses In ...mentioning
confidence: 88%
“…In murine models, the exhausted T cell compartment in the TME can be replenished with a pool of stem-like Tcf7+ effector CD8+ T cells from the tumour-draining LN [ 94 ]. In humans, breast cancer patients with low TIL levels (<5%) at their primary tumour express higher levels of immune checkpoint molecules, including CTLA-4 and OX-40, in their tumour-draining LNs than patients with high TIL levels (>50%) [ 57 ], leading to the conjecture that the tumour-draining LN is one source of TILs and that T cell deactivation in the tumour-draining LN may contribute to a dampened immune response at the primary tumour site. TCR sequencing of the primary tumour and tumour-draining LN T cells revealed extensive clonotype overlap between expanded CD8+ T cells from both sites.…”
Section: Lymph Nodes: the Immune Capital Of Anti-tumour Responses In ...mentioning
confidence: 99%
“…The immune system plays a key role in cancer, but differences between individuals can lead to different outcomes. A high number of tumor-infiltrating lymphocytes (TIL) in triple-negative breast cancer (TNBC) are related to a better prognosis ( 1 ), although not in all patients ( 2 ). Several factors influence a good antitumoral immune response, such as the recognition of neoantigens, the presence of immunomodulatory mediators, or the cellular composition and diversity of TIL, including the presence of antigen-presenting cells (APC) such as dendritic cells (DC) or B cells.…”
Section: Introductionmentioning
confidence: 99%